Dampak Anggaran Biaya Operasional terhadap Profitabilitas Perusahaan - Muammar khadafi; Saidatun Nuri; Intan Maulina; Rikeniateni Rikeniateni; Munasarah Munasarah (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2025)
This study examines the impact of operational cost budgeting on company profitability in Indonesia through a literature review approach. Analysis of various studies over the past decade reveals a significant positive relationship between effective operational cost budget management and increased profitability. However, this relationship is complex and influenced by factors such as the optimal point of budget control, management information systems, and external conditions like the COVID-19 pandemic. Variations across industry sectors were also found, with the manufacturing sector showing the strongest correlation. This research identifies best practices in budgeting as well as implementation challenges in Indonesia. These findings provide important implications for financial management practices and open directions for further research in the context of Indonesia's dynamic business environment.